Platelet activation In mice and human Helicobacter pylori infection. - Elizalde, J I (1997)
Extracts of Helicobacter pylori (HP) have been shown to induce leukocyte adhesion in mesenteric venules, but the effects of HP infection on gastric microvessels are unknown. Inflammatory cell interactions in the gastric microcirculation were studied by intravital videomicroscopy in mice inoculated with either saline or fresh isolates of HP. Platelet aggregates were detected and quantified in murine portal blood, while endothelial P-selectin expression was determined using the dual radiolabeled mAb technique. Platelet activation and aggregation were studied in HP-infected patients and controls by measuring the platelet-aggregate ratio and platelet P-selectin expression. HP infection induced a marked increase in the flux of rolling leukocytes and the appearance of platelet and leukocyte- platelet aggregates in murine gastric venules. The HP-induced rolling and platelet aggregate formation was abrogated by mAbs against L- or P-, but not E- selectin. Endothelial cell expression of P-selectin was not altered, but platelet P-selectin expression was enhanced in HP-infected mice. Circulating platelet aggregates and activated platelets were also detected in HP-infected patients. These findings indicate that platelet activation and aggregation contribute to the microvascular dysfunction and inflammatory cell recruitment associated with HP infections.